Результаты испытаний молниеотводов с универсальными зажимами апериодическими импульсами тока искусственной молнии с нормированными по международным стандартам амплитудно-временными параметрами - Баранов, Михаил Иванович; Колиушко, Георгий Михайлович; Кузьминский, Евгений Викторович; Мысюк, Юрий Игорьевич; Рудаков, Сергей Валерьевич (НТУ "ХПИ", 2015)
Приведены результаты прямого воздействия на круглые медные и оцинкованные стальные молниеотводы с плоскими медными, оцинкованными стальными и нержавеющими стальными универсальными зажимами специального профиля апериодических импульсов тока искусственной молнии нормированной по международному IEC 62305-1: 2010, российскому национальному ГОСТ Р МЭК 62305-1-2010 и немецкому национальному DIN EN 50164-1:2008 стандартам временной формы 10 мкс/350 мкс и амплитуды (50-100) кА с заданными этими стандартами допусками.

Purpose. Test in obedience to the requirements of row of operating foreign standards of round metallic lightning-rods with the flat metallic universal clamps of the special type on firmness to direct action of аperiodic impulses of current of temporal form 10/350 μs by amplitude of 50 кА (N−class) and 100 кА (H−class). Methodology. The order of leadthrough of these tests is certain the followings normative documents: International IEC 62305-1: 2010, Russian national GOST R IEC 62305-1-2010 and German national DIN EN 50164-1:2008 Standards. Results. Conducted on a powerful high-voltage pulsed current of artificial linear lightning with the peak-temporal parameters and admittances of test rationed on the indicated foreign standards rationed that all of the lightning-rods tested in collection with universal clamps, isolating holders and ceramic elements of roof of technical building were survive electrodynamics and electrothermal action of in-use single short blow of an artificial storm digit. Originality. First in domestic practice the similar model tests of lightning-rods are conducted with universal clamps, executed from different explorer materials, on firmness to flowing to on by it the indicated large impulsive currents of artificial lightning. Practical value. Real firmness to lightning of round copper and zincked steel lightning-rods is certain with the flat copper, zincked steel and non-rusting steel universal clamps of the special execution.
Results of tests of lightning-rods with universal clamps by the aperiodic impulses of current of artificial lightning with the peak-temporal parameters rationed on foreign standards
Keywords: металлические молниеотводы; генератор апериодических импульсов тока; молниестойкость; искусственная молния; metallic lightning-rods; generator of aperiodic impulses of current; firmness to lightning